An Introduction to the Prevention of Domestic Violence Act of Sri Lanka - Wijeyesekera, Rose (My University, 2011)
It is undisputed that the numbers of people particularly women and children, who are subjected to violence at the hands of those who are close to them or somebody who is supposed to protect them, are on the increase. In the recent past, there has been growing concern and recognition of the high rate of occurrence of domestic violence all over the world. Violent behaviour against any person results in the denial of fundamental human rights affirmed in international instruments such as the Universal Declaration of Human rights (UDHR), the CEDAW, and the Convention on the Rights of the Child (CRC). Several countries have introduced new laws relating to domestic violence, some of which are gender based while some are gender neutral. Prevention of Domestic Violence Act of Sri Lanka is one such gender neutral statute deals with the issues of domestic violence. This article intends to analyze some features of this statute in comparison with South African and Malaysian Statutes on the subject.